Gut-brain axis and vascular dementia: a review on mechanisms and Chinese herbal medicine therapeutics - Dexiu Wang; Huiying Yao; Luoqi Wang; Bowen Lu; Wenkai Liu; Jinghan Li; Yujin Gong; Yuhao Cai; Yuehan Li; Xin Cai; Rui Zhang; Rui Zhang (Frontiers in Microbiology)
Vascular dementia (VD), the second most prevalent form of dementia among the elderly population, is a cerebrovascular disorder characterized primarily by cognitive impairment. Emerging evidence has revealed that intestinal flora dysbiosis may be implicated not only in gastrointestinal (GI) pathologies but also in central nervous system (CNS) disorders, including VD. The gut-brain axis (GBA) serves as a critical bidirectional pathway through which intestinal flora influences brain physiology and function. Notably, accumulating studies have demonstrated the therapeutic potential of Chinese herbal medicine (CHM) in VD management via modulation of gut microbial composition. This review synthesizes current understanding of the VD- intestinal flora relationship mediated by the GBA, while systematically evaluating evidence for CHM interventions that ameliorate VD through intestinal flora regulation. These insights may offer novel perspectives and methodological approaches for both fundamental research and clinical management of VD.